METHOD AND MEANS TO MAINTAIN GROUND TAKEOFF DISPLACEMENTS OF TRANSPORT CATEGORY AIRCRAFT MODIFICATIONS AT BASE VARIANT LEVEL - Людмила Валерьевна Капитанова; Виктор Иванович Рябков (Авіаційно-космічна техніка та технологія, 2018)
The problem of improving the takeoff and landing runway characteristics of heavier modifications of the transport category aircraft was further developed on the condition of equality of ground displacements of heavier modifications and their base variant by creating a method of formation of the “take-off mass - thrust-to-weight ratio” characteristics and using the fundamentally new local structures of additional slotted spoilers in extendable flaps and additional energetic chambers in landing gear shock absorber systems. The development of such a method and the use of additional slotted spoilers and energetic chambers in the shock absorber systems can provide for the basing of heavier modifications at the aerodromes assigned for the base aircraft.